Effect of polycarbonate structure and reduction time on graphene oxide dispersion. (26th May 2015) - Lee, Bom Yi; Park, Ju Young; Kim, Youn Cheol
<x xml:space="preserve">Abstract</x> Polycarbonate (PC)/graphene oxide (GO) composites with different GO reduction time and PC types were prepared by using a twin screw extruder at 260 °C after solution mixing with chloroform. The chemical reaction degree of PC/GO composites with GO reduction time was confirmed by C–H stretching peak at 3000 cm −1, and the chemical reaction degree decreased with GO reduction time. The slope for storage (G′) versus loss (G″) modulus plot decreases with an increase in heterogeneous property of the polymer melts. So we can check the GO dispersion of the PC/GO composites using by the slop for G′–G″ plot. According to the G′–G″ slopes for PC/GO composite with GO reduction time, GO was well dispersed within PC matrix when the reduction time decreased. It was re‐confirmed by atomic force microscope (AFM) results. Based on the degradation temperature by Thermogravimetric analysis, G′–G″ slopes, and surface roughness by AFM, the branched PC was better than linear PC for the GO dispersion within PC matrix. The fact was also confirmed by tensile test results that the Young's modulus increased with the improvement of GO dispersion. Copyright © 2015 John Wiley & Sons, Ltd.